To solve for the expression A such that the equation \( A = 5 - \frac{1}{13} \) holds true, let's first simplify the right side of the equation:
-
Convert \( 5 \) to a fraction with a denominator of \( 13 \):
\( 5 = \frac{65}{13} \). -
Now the equation becomes:
\( A = \frac{65}{13} - \frac{1}{13} \). -
Combine the fractions:
\( A = \frac{65 - 1}{13} = \frac{64}{13} \).
Now, let's analyze the given expressions to determine which matches \( A = \frac{64}{13} \):
-
A= \( \frac{12}{3} - \frac{1}{3} \)
- Simplifying gives: \( 4 - \frac{1}{3} = 4 - 0.33 \) (not \( \frac{64}{13} \))
-
A= \( -\frac{12}{3} + \frac{1}{3} \)
- Simplifying gives: \( -4 + \frac{1}{3} \) (not \( \frac{64}{13} \))
-
A= \( \frac{12}{3} + \frac{1}{3} \)
- Simplifying gives: \( 4 + \frac{1}{3} = \frac{12 + 1}{3} = \frac{13}{3} \) (not \( \frac{64}{13} \))
-
A= \( \frac{15}{3} + \frac{1}{3} \)
- Simplifying gives: \( 5 + \frac{1}{3} = \frac{15 + 1}{3} = \frac{16}{3} \) (not \( \frac{64}{13} \))
None of these expressions equal \( \frac{64}{13} \), indicating there might be a mistake in either the problem options or the calculations. However, if we recap the problem strictly based on the calculations: the only expression that leads correctly to the value that we need is \( A = \frac{64}{13} \), and check if that equates with given options, it doesn't.
This overall lead us to conclude that none of the provided options give a correct expression for A to satisfy \( A = 5 - \frac{1}{13} \). Please check the context or options again for potential typos.